Historical dictionary of Taiwan (Republic of China) - Copper, John Franklin (Historical dictionaries of Asia, Oceania, and the Middle East, 2015)
This fourth edition of Historical Dictionary of the Taiwan (Republic of China) covers its history through a chronology, an introductory essay, appendixes, and an extensive bibliography.